Phytochemical Testing and In Vitro Anti-inflammatory Activity on Ethanol Extract of Akar Kuning (Arcangelisia flava L) Stems from West Kalimantan - Gusti Eva Tavita; Desriani Lestari; Riza Linda; Rita Kurnia Apindiati; Rafdinal Rafdinal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The akar kuning plant (Arcangelisia flava L) from the Menispermaceae family is one of the Bajakah plant groups, which propagate among large trees and are commonly found in tropical forests in the West Kalimantan region. The purpose of this study was to determine the phytochemical compound and activity of anti-inflammatory from the akar kuning stem ethanol extract through the stabilization ability of the human red blood cell membrane (HRBC) in vitro. The akar kuning plant was taken from the forest of the Kapuas Hulu region, dried and mashed first and then extracted by maceration using the organic solvent ethanol. The ethanol extract obtained was concentrated using a rotary evaporatory, then a sample solution of akar kuning ethanol extract was made at several concentrations. Based on the results of phytochemical testing, this plant contained flavonoids, tannins, alkaloids and saponins. Anti-inflammatory activity testing using rabbit blood and using diclofenac sodium as a positive control. The measurement results showed the anti-inflammatory activity of the ethanol extract of the yellow root plant at concentrations of 50, 100, 150, 200 and 250 mg/mL were 28.77, 39.45, 57.53, , 62.80 and 75.50%, while the percentage of HRBC stabilization of the positive control was at the same concentration were 34.55, 46.34., 56.56, 69.88 and 87.33%.